Mass Media Exposure and Women’s Household Decision-Making Capacity in 30 Sub-Saharan African Countries: Analysis of Demographic and Health Surveys - Seidu, Abdul-Aziz; Ahinkorah, Bright Opoku; Hagan, John Elvis; Ameyaw, Edward Kwabena; Abodey, Eric; Odoi, Amanda; Agbaglo, Ebenezer; Sambah, Francis; Tackie, Vivian; Schack, Thomas (Frontiers in Psychology, 2020)
Background Women’s household decision-making capacity is an essential component of their empowerment which include decisions related to personal health care, large household purchase and family visitations. Despite some research acknowledging mass media influences on women empowerment, including their ability to take household decisions, empirical data through multi-country comparison on women mass media exposure and women’s decision making capacity are sparse. This study sought to assess the association between exposure to newspaper, television and radio and women’s household decision-making capacity in 30 countries in sub-Saharan Africa (SSA). Materials and Methods Data from current Demographic and Health Surveys (DHS) conducted from 30 countries in SSA from January 1, 2010 to December 31, 2016 were used. Binary Logistic Regression analysis was used to assess the association between mass media exposure and women’s household decision-making capacity in SSA. Results were presented using crude odds ratios (COR) and adjusted odds ratios (AOR). Results Women who watch television almost every day had higher capacity to take household decisions, compared to those who do not watch television at all. Women who read newspaper/magazine less than once a week were less likely to take household decisions compared to those who never read newspaper/magazine. However, there was no association between exposure to radio and household decision-making capacity. Regarding the covariates, age, level of education, wealth index, occupation and parity showed significant associations with women’s household decision-making capacity. Conclusion Findings stressed the positive contribution of mass media in enhancing women’s household decision-making capacity in SSA. Viewing television, a model of mass media, is a very powerful conduit to enhance the household decision-making capacity of women. The use of mass media, especially television in communicating the relevance and ways of achieving household decision-making capacity for all women in SSA is paramount and perhaps, other low and middle-income regions of the world. Interest groups that require greater attention are women with less exposure to television as well as women in their early reproductive age, the poor, women who are not working and rural residents.